2020
DOI: 10.3390/cells9010176
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Gut Microbiota and Non-Alcoholic Fatty Liver Disease: Three Parts of the Same Axis

Abstract: Non-Alcoholic Fatty Liver Disease (NAFLD) is the most common liver disease in the world. NAFLD is principally characterized by an excessive fat accumulation in the hepatocytes. Diet is considered as one of the main drivers to modulate the composition of gut microbiota, which participate in different processes, affecting human metabolism. A disruption in the homeostasis of gut microbiota may lead to dysbiosis, which is commonly reflected by a reduction of the beneficial species and an increment in pathogenic mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 98 publications
(167 reference statements)
3
65
1
Order By: Relevance
“…Dysbiosis of the gut microbiota, which is an alteration of the bacterial intestinal composition, reflexed a decreasing number of species related to an increased intestinal barrier permeability, thus allowing the bacterial translocation and causing endotoxemia [211], which is an important risk factor for obesity development and related metabolic diseases, as it is confirmed in different studies [212]. The constant flow in the composition of the gut microbiota is due to changes in diet, environmental factors and lifestyle [213]. As an intrinsic factor, the immune system health may cause changes in gut microbiota composition that may promote the proliferation of specific bacterial species which could be harmful due to the immune deficiency or hyperimmunity [214].…”
Section: Gut Microbiota Dysbiosismentioning
confidence: 94%
“…Dysbiosis of the gut microbiota, which is an alteration of the bacterial intestinal composition, reflexed a decreasing number of species related to an increased intestinal barrier permeability, thus allowing the bacterial translocation and causing endotoxemia [211], which is an important risk factor for obesity development and related metabolic diseases, as it is confirmed in different studies [212]. The constant flow in the composition of the gut microbiota is due to changes in diet, environmental factors and lifestyle [213]. As an intrinsic factor, the immune system health may cause changes in gut microbiota composition that may promote the proliferation of specific bacterial species which could be harmful due to the immune deficiency or hyperimmunity [214].…”
Section: Gut Microbiota Dysbiosismentioning
confidence: 94%
“…Overall, oxidative imbalance, low-grade inflammation, plasmatic and/or hepatic dyslipidaemia, impaired incretin effect, gut microbiota changes, endoplasmic reticulum stress and/or mitochondrial dysfunction are common cellular denominators of obesity-related metabolic diseases. [28][29][30][31] Similar to that in humans, chronic consumption of diets rich in fat and sugar leads to deleterious metabolic effects in rodents, despite differing responsiveness among species and strains. Thus, paradigms of longstanding free access to palatable calorie-dense food are widely used in preclinical research to model the progression of obesity and related comorbidities.…”
Section: Diet As a Driving Force For The Continuum Of Obesity-relatmentioning
confidence: 99%
“…In the present study, the results illustrated that ANGP TL8 is a possible mediator of the crosstalk between the liver and the gut. There are multiple intestinal factors that act on the liver through the portal circulation, such as LPS and SCFAs, whereas bile acids are the only well-established hepatogenic molecules that are able to regulate the gut microbiota from the liver (Quesada-Vazquez et al 2020). ANGPTL8 is a novel hepatokine that exists in the circulatory system and is regarded as a hormone that is directly associated with the endocrine system.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that the liver tissue influences the structure of the gut microbiota through secreting bile acids. Abnormal secretion of bile acids plays an important role in the dysbiosis of gut microbiota (Quesada-Vazquez et al 2020).…”
Section: Introductionmentioning
confidence: 99%